Application of covering rough granular computing model in collaborative filtering recommendation algorithm optimization. (January 2022) - Yan, Hong Can; Wang, Zi Ru; Niu, Jia Yang; Xue, Tao
Abstract: Data sparseness will reduce the accuracy and diversity of collaborative filtering recommendation algorithms. In response to this problem, using granular computing model to realize the nearest neighbor clustering, and a covering rough granular computing model for collaborative filtering recommendation algorithm optimization is proposed. First of all, our method is built on the historical record of the user's rating of the item, the user's predilection threshold is set under the item type layer to find the user's local rough granular set to avoid data sparsity. Then it combines the similarity between users. Configuring the covering coefficient for target user layer, it obtained the global covering rough granular set of the target user. So it solved the local optimal problem caused by data sparsity. Completed the coarse–fine-grained conversion in the covering rough granular space, obtain a rough granular computing model with multiple granular covering of target users, it improved the diversity of the recommendation system. All in all, predict the target users' score and have the recommendation. Compared experiments with six classic algorithms on the public MovieLens data set, the results showed that the optimized algorithm not only has enhanced robustness under the premise of equivalent time complexity, but also has significantly higher recommendation diversity as well as accuracy.